Nuclear farnesoid X receptor protects against bone loss by driving osteoblast differentiation through stabilizing RUNX2 - Qi Dong; Haoyuan Fu; Wenxiao Li; Xinyu Ji; Yingchao Yin; Yiran Zhang; Yanbo Zhu; Guoqiang Li; Huiyang Jia; Heng Zhang; Haofei Wang; Jinglue Hu; et al. (Bone Research)
Abstract The delicate balance between bone formation by osteoblasts and bone resorption by osteoclasts maintains bone homeostasis. Nuclear receptors (NRs) are now understood to be crucial in bone physiology and pathology. However, the function of the Farnesoid X receptor (FXR), a member of the NR family, in regulating bone homeostasis remains incompletely understood. In this study, in vitro and in vivo models revealed delayed bone development and an osteoporosis phenotype in mice lacking FXR in bone marrow mesenchymal stem cells (BMSCs) and osteoblasts due to impaired osteoblast differentiation. Mechanistically, FXR could stabilize RUNX2 by inhibiting Thoc6-mediated ubiquitination, thereby promoting osteogenic activity in BMSCs. Moreover, activated FXR could directly bind to the Thoc6 promoter, suppressing its expression. The interaction between RUNX2 and Thoc6 was mediated by the Runt domain of RUNX2 and the WD repeat of Thoc6. Additionally, Obeticholic acid (OCA), an orally available FXR agonist, could ameliorate bone loss in an ovariectomy (OVX)-induced osteoporotic mouse model. Taken together, our findings suggest that FXR plays pivotal roles in osteoblast differentiation by regulating RUNX2 stability and that targeting FXR may be a promising therapeutic approach for osteoporosis.